Evaluation of Byproducts of Some Minor Millets for Chemical Composition,Mineral Profile and In Vitro Gas Production Kinetics - T.V.Girisha; V .Nagabhushana; T. Thirumalesh; K.S. Giridhar; A.M.Kotresh; R. Jayashree; N.B.Shridhar; K.C.Veeranna (Indian Journal of Animal Nutrition, 2025)
An in vitro evaluation of byproduct of selected minor millets by gas production technique followed by an in vivo evaluation of Browntop millet (Brachiariaramosa) byproduct based CFM by twelve-week feeding and metabolism trial in sheep was conducted. In vitro study revealed that ME(MJ/kg) and IVDOM(%) of Browntop (6.81 and 53.95) and Littlemillet (6.81 and 53.09) byproduct were similar whereas lower values were found in Foxtail(5.04 and 41.70), Kodomillet (5.00 and 40.26), Prosomillet (5.23 and 43.47) and poor in Barnyard (2.90 and 30.79). In vitro gas production kinetics study revealed that readily soluble fraction ‘a’ value was not detectable whereas, insoluble but fermentable fraction “b” was significantly (P0.05) in mean DMI(83.78;82.99) as compared to T1(86.31g/kg W0.75). Intake of nutrients, except EE, were comparable. Digestibility of DM,CP,CF,NFE,NDF,ADF,C and HC was similar However, digestibility of OM and EE (P0.05).It is concluded BTMBP and LTMBP were found to be nutritionally better than FXMBP,KDMBP,PSMBP. BYMBP was nutritionally poor.